FAKTOR-FAKTOR YANG MELATARBELAKANGI PERILAKU IBU DALAM PEMBERIAN ASI EKSKLUSIF PADA BAYI USIA 0-6 BULAN DI WILAYAH PUSKESMAS SUMBERSARI KABUPATEN JEMBER - Kustin Kustin (Jurnal Kesehatan dr. Soebandi, 2014)
One of the causes of death and morbidity in infants is lack of calories and protein which are found in infants, because many breast milk is replaced with formula milk. The purpose of this study was to identify the factors underlying the behavior of mothers in exclusively breastfeeding for infants 0-6 months in the area of ​​Sumbersari Health Center, Jember Regency. The research design used is descriptive with cross sectional approach, the population is mothers who have infants aged 0-6 months in the area of ​​Sumbersari Health Center in Jember Regency as many as 82 respondents. Sampling was done in total sampling population, the independent variables in this study were knowledge, husband's attitudes and family attitudes, while the dependent variable was maternal behavior in the success of exclusive breastfeeding. Data collection was carried out by distributing questionnaires and from posyandu books. The study was conducted in May to August 2014. The results showed that the majority of respondents' knowledge was good as many as 32 people (72.72%), the attitude of most husbands were positive as many as 58 people (70%), family attitudes were mostly positive as many as 56 people (59.09%) and maternal behavior mostly does not exclusively breastfeed (54.54%). From this study it can be concluded that the factors underlying the behavior of mothers in exclusive breastfeeding are largely motivated by predisposing factors (knowledge), which is a very important domain in shaping one's actions. It is recommended to the public to broaden their horizons by attending counseling at the Puskesmas or asking health workers about the importance of exclusive breastfeeding, and to health workers to further enhance education on exclusive breastfeeding.